Early Risk Stratification in a High-Mortality Study of Adult Trauma Patients: A Comparative Validation of RTS, SI, and ISS - Denny Prasetyo; Arie Zainul Fatoni; Ristiawan Muji Laksono; Buyung Hartiyo Laksono (HM Publisher, 2025)
Introduction: Accurate, early risk stratification is paramount in managing severe trauma, especially in resource-limited settings. This study aimed to compare the predictive performance of the revised trauma score (RTS), shock index (SI), and injury severity score (ISS) for in-hospital mortality in a group of severely injured adult trauma patients at a tertiary center in Indonesia. Methods: A retrospective analysis was conducted on a purposively selected study population of 100 adult trauma patients (age 20-60) admitted to the Emergency Department of Dr. Saiful Anwar Regional General Hospital over a three-month period in 2023. This selection method yielded a high-mortality sample (50% mortality) to ensure sufficient statistical power for analyzing fatal outcomes. The predictive performance of RTS, SI, and ISS was evaluated using individual logistic regression models. Discriminatory ability was assessed by calculating the area under the receiver operating characteristic curve (AUC-ROC) for each score. Model calibration was evaluated using the Hosmer-Lemeshow goodness-of-fit test. Results: All three scoring systems were significant predictors of mortality in individual regression analyses. The injury severity score (ISS) demonstrated the highest discriminatory power for predicting mortality with an AUC of 0.88 (95% CI, 0.81-0.95). The revised trauma score (RTS) also showed good discrimination with an AUC of 0.83 (95% CI, 0.75-0.91). The Shock Index (SI) was a significant predictor but had the most modest discriminatory ability with an AUC of 0.76 (95% CI, 0.67-0.85). All models were well-calibrated. Conclusion: In this study of severely injured adult trauma patients, the anatomically-based ISS was the most accurate predictor of mortality. The physiological scores, RTS and SI, remain valuable for their utility in rapid, initial patient assessment. The findings support a complementary approach, using the simple physiological scores for immediate triage and the more comprehensive ISS for definitive prognostication.